Guidelines for completion of thesis educational qualification level – Master's degree in knowledge area 12 "Information technology" - Litvinova, U. S.; Cherednichenko, O. Yu.; Shmatko, O. V.; Moskalenko, Valentina Volodymyrovna; Kopp, A. M. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The guidelines contain a description of the requirements for the mandatory structure and minimum content of explanatory notes of master's theses for students studying in the speciality 121 "Software Engineering" of the educational programme "Software Engineering".
Keywords: guidelines; diploma works; magistracy; information technology; software engineering; research activity